Compaction of a cambisol caused by forest harvesting machines with spatialized geostatistics Compactação de um cambissolo causada por máquinas de colheita florestal espacializada com geoestatística - Lopes E.S. (2016)
The objective of this study was to evaluate the impact and the extent which penetration resistance (PR) of a Humic Cambisol (HC) is affected by traffic of timber harvesting machines in stands of Pinus taeda L., using geostatistics methods. The study was conducted in areas of the forestry company located in the Santa Catarina State, Brazil. The treatments were derived from simulation of different machines traffics intensities. The soil penetration resistance (PR) measures were taken in wheel tracks trails and in horizontal intervals of 0.25 up to 1.00 m, and in between the tracks, making a grid of 5 x 20 m, with 55 points per treatment and 330 in total, being the data collected at intervals of 0.01 up to 0.80 m of depth. Data were analyzed with descriptive statistics and were adjusted semivariogram models for the spatial dependence analysis. The results showed a great range and variation of compaction dates. Gaussian models predominated in adjusted variogram models, with strong spatial dependence degree, from 0.774 to 0.929, and range ranged from 0.83 to 2.12 m. The geostatistics methods allowed to determine the extent of the traffic effects, and may provide support for improvement soil management and planning of forest operations.